Loess soil distribution and properties in Mongolia - Ochirbat Batkhishig; Svetlana Timireva; Turmunkh Telmen; Yuri Kononov; Maamkhuu Zolzaya; Tserengunsen Purevdorj (Proceedings of the Mongolian Academy of Sciences)
Loess and loess-like soil formations are distributed in 3 regions across Mongolia. The lower part of the Orkhon and Selenge river basin in North Mongolia is the main loess area and another two are located in east Mongolia, in the Onon and Ulz river basins and the Khalka Gol river area. Loess-like soil covers a total of 109,000 sq.km or 6.95 per cent of the territory of the country. Loess soil properties have been studied on the basis of 8 sections and 83 samples. Fine sand fraction is predominant in the loess granulometric composition and its mean value is 51.3 per cent, and silt content mean value is about 34.9 per cent. A typical loess is a non-stony silt or fine sand, but there are also gravel loess. The average stone gravel content in the loess sediments is 8.1 per cent, sandy loess doesn’t contain any stone, but coarse fragment is high (20.5 per cent) in gravel loess. There is higher sand content (57.0 per cent) in gravel loess as compared to sandy loess (47.4 per cent). Mongolian loess soil average calcium carbonate content is 2.9 per cent, and Organic Matter (0.93 per cent) is higher than Chinese loess (0.41 per cent). Using 14C isotope data analysis and sediment properties we have tried to define the loess stratigraphy. Lower base section of fine sand silty loess sediments or about 1-3 meter thick layers were mostly formed during the mid-Holocene (7.5-3.0 ka) period. Upper parts of silty loess or 1.0-0.7 meter top layers were accumulated in the late Holocene (3ka BP to present) period. Kastanozem topsoil humus horizon (15-30 cm) formation starts at 1.5-1.0 ka BP. Mid-Holocene period probably witnessed the most active loess accumulation with a warm and dry windy condition prevailing. Sandy loess with a thickness of 1-2 meters predominate in Mongolia, and in some places loess thickness reaches up to 20-30 meters.